Self-Efficacy and Student Achievement for Enhancing Career Readiness: The Mediation of Career Maturity - Mar'atus Sholikah; Muhyadi Muhyadi; Setyabudi Indartono; Olzhas B. Kenzhaliyev; Gulzhaina K. Kassymova (Jurnal Pendidikan Teknologi dan Kejuruan, 2021)
Increasingly dynamic and volatile employment trends and the rapid development of the globalization era resulted in the transformation of the world of work to be faster, diverse and challenging to predict. Therefore, individuals are encouraged to have a flexible attitude to adapt and work according to their current career development. The purpose of this study was to determine the effect of self-efficacy and academic achievement on career readiness outside the profession through career maturity as a mediator. The survey method with a quantitative approach was applied in this study using a sample of 80 students. This study selected the sample based on purposive sampling on all Office Administration students of the State University of Semarang. Data analysis performed using Smart PLS 3.0. This study tested the proposed model through two aspects: measurement and structural models. This study found that self-efficacy and career maturity positively and significantly affected career readiness outside the profession. Academic achievement, in this case, also affects career readiness, but not considerably. The role of career maturity as mediation has an effect on self-efficacy on career readiness partially. Thus, it can conclude that self-efficacy influences career readiness. These findings make an essential contribution for lecturers and institutions to pay more attention to student career readiness so that their opportunities as university graduates to be accepted into the world of work can run smoothly.